Problem Teoritik Dan Implikasi Praktis Atas Perubahan Keputusan Tata Usaha Negara - Tohadi Tohadi; Frieda Fania; Dadang Gandhi (Fakultas Hukum Universitas Islam Indonesia, 2019)
The change in the meaning of the State Administration Decree (KTUN) as stipulated in Article 87 of the Government Administration Act raises academic questions when the change had not been made through the amendment to the PTUN Law. This study discusses first, analysis on the change in the meaning of KTUN according to Law No. 30 of 2014 in terms of the theory of repeal and changes in legislation. Second, change in the meaning of KTUN according to Law No. 30 of 2014 in terms of the principles of the statutory rules. Third, implications of changing the meaning of KTUN according to Law No. 30 of 2014 against the absolute competence of PTUN. This is a normative study with qualitative analysis. The results of the study concluded, firstly, based on the theory of changes in legislation, the amendment to the provision of KTUN is not at all appropriate. Because it is done through a law that (the substantive content) is different. Second, the principles of statutory rules, namely lex specialis derogat legi generali, and lex posteriori derogat priori legi are not applicable to the enactment of Article 87 of Law No. 30 of 2014. Third, amendment to the provision of the KTUN according to Article 87 of Law No. 30 of 2014 has expanded the absolute authority of the PTUN to examine, to prosecute, and to decide the unlawful acts committed by the state officials that were previously the authority of the general court.